Update on biomarkers of hepatocellular carcinoma - Chaiteerakij, Roongruedee; Addissie, Benyam D; Roberts, Lewis R (Clinical gastroenterology and hepatology, 2015)
New biomarkers of hepatocellular carcinoma (HCC) have been identified using advanced genomic, proteomic, and metabolomics technologies. These are being developed not only for use in diagnosis of HCC, but also in prediction of patient and treatment outcomes and individualization of therapy. Some HCC biomarkers are currently used in surveillance to detect early stage HCCs and reduce mortality. Further studies are needed to determine whether the recently identified HCC biomarkers can be used in clinical practice; most are only in phase 1 or 2 studies. The diagnostic and predictive abilities of biomarkers are limited by the heterogeneous nature of HCCs; there is no perfect single biomarker of this tumor. To improve performance, combinations of biomarkers (panels), or combinations of biomarkers and clinical parameters or laboratory test results, might be required. We describe recently discovered biomarkers of HCC and discuss challenges to their development and application.